Critical overview of the current status of treatment of upper digestive tract cancer - Wiktor Szawłowski, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2000)
Results of surgical treatment of advanced upper digestive tract cancers (esophagus, stomach, pancreas, external bile ducts, liver) are bad. Therefore the current standard of treatment constitutes combimed modality approach associating surgery with chemotherapy in different combinations. In esophageal carcinoma the current trend is focused on preoperative radio– and /or chemotherapy or definitive chemo-radiotherapy with high dose rate (HDR) brachytherapy. In gastric cancer the main aim constitutes the promotion of early diagnosis, optimalization of surgical treatment (gastrectomy with regional lymphadenectomy) and prospective trials of adjuvant chemotherapy. In pancreatic cancer the progress in treatment results can be expected due to optimalization of surgical treatment (pancreatectomy with regional lymphadenectomy) and further prospective studies on indications for definitive brachytherapy HDR with chemo-radiotherapy. Gemcytabine is also considered as a new propective drug for both the first and second line palliative therapy. In extrahepatic bile ducts cancer the need for optimal surgical approach (resection when feasible with lymphadenectomy (should be approached and prospectively the chemo-radiotherapy should be investigated. In primary liver cancers the progress can be expected using combination of surgery and chemotherapy.